2022
DOI: 10.1371/journal.pone.0268833
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification for hospital-acquired venous thromboembolism in medical patients (RISE): Protocol for a prospective cohort study

Abstract: Background Hospital-acquired venous thromboembolism (VTE) is one of the leading preventable causes of in-hospital mortality. However, its risk assessment in medically ill inpatients is complicated due to the patients’ heterogeneity and complexity of currently available risk assessment models (RAMs). The simplified Geneva score provides simplicity but has not yet been prospectively validated. Immobility is an important predictor for VTE in RAMs, but its definition is inconsistent and based on subjective assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Even though guidelines, including those from the American College of Chest Physicians or the National Institute for Health and Care Excellence, encourage the use of RAMs to identify medical inpatients at high VTE risk, our results emphasize the need for more accurate risk prediction strategies, as already advocated by others . For example, it is unclear whether the use of objective mobility measures or artificial intelligence–based models could improve VTE risk prediction . In addition, the clinical benefit associated with applying RAMs is unclear .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though guidelines, including those from the American College of Chest Physicians or the National Institute for Health and Care Excellence, encourage the use of RAMs to identify medical inpatients at high VTE risk, our results emphasize the need for more accurate risk prediction strategies, as already advocated by others . For example, it is unclear whether the use of objective mobility measures or artificial intelligence–based models could improve VTE risk prediction . In addition, the clinical benefit associated with applying RAMs is unclear .…”
Section: Discussionmentioning
confidence: 99%
“… 8 For example, it is unclear whether the use of objective mobility measures or artificial intelligence–based models could improve VTE risk prediction. 19 , 31 In addition, the clinical benefit associated with applying RAMs is unclear. 8 , 25 Except for a single randomized trial that showed a reduction in VTE rates with a computer-alert program incorporating the Kucher RAM, 32 no prospective comparative study has, to our knowledge, demonstrated improved clinical or economic outcomes with the application of RAMs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers support that the probability (the "risk") of PE can be objectified successfully in both out-of-hospital and in-hospital patients [23]. Most of these studies are retrospective in nature and/or non-consecutive patients were included [20][21][22], while a large prospective cohort study will improve our knowledge about the risk stratification and the diagnostic dilemmas in hospitalised patients with PE [24].…”
Section: Introductionmentioning
confidence: 99%